KESESUAIAN ALAT DAN MESIN UNTUK PENGUSAHAAN HUTAN TANAMAN INDUSTRI - Sri Sutopo; Djaban Tinambunan (Jurnal Penelitian Hasil Hutan, 1995)
Several short  investigations   have  been conducted   lo find the suitability  of equipment and machine   used in foreste  estate  operations.   Original  condition  of  land,  soil cultivation practices, and the productivity  of various  equipment   were also collected.The areas  used  for linber   estate  are  usually   alang-alang  grassland  with  the alang-alang densitv  of around  two million  stems/ha,   the average slope of  8%,   consited  of red yellow to red brown podsolik soils. the soil is plowed  twice hy  using  disc plow of 70 cm diameter  with the plowing  depth  of  20-30 cm.   and then harrowed  by using  disc  harrow of 46 cm diameter  with the harrowing  depth  of  15-20  cm.The  efective  power  used for plowing  is around  25 HP and  for  harrowing  is  around 19 HP. Therefore  the engine power  required  (with  50%  efficiency)  is around 50 HP.   For harrowing with  this level of power,   the  harrow  can  be  extended  up  10   4.8  m  wide  to  increase power efficiency,Felling productivities  by using  chainsaw and feller-buncher    are  7.096  and  7. 708 m3/hour, respectivelv,   The  difference  between  these  two  figures   is  not   significant.    While the skidding productivities   by  using  tractor   (140 HP)  and feller-buncher   are  4.929  and  5.140  m3/hour, respectively,   The  difference between this two figures  is highly  significant.Tge  relationship  between  the  power   of  tractor   and  productivity   is  linear  with  higher productivity   when the power  is larger.   Other  result shows that the tractor  used   are mostly too large and,  therefore,  need the  modification  of plow  and harrow combinations.